UNJUK KERJA REAKTOR PLASMA DIELECTRIC BARRIER DISCHARGE UNTUK PRODUKSI BIODIESEL DARI MINYAK KELAPA SAWIT - Ardian Dwi Yudhistira; Istadi Istadi (TEKNIK, 2013)
Biodiesel is one of alternative renewable energy source to substitute diesel fuel. Various biodiesel productionprocesses through transesterification reaction with a variety of catalysts have been developed by previousresearcher. This process still has the disadvantage of a long reaction time, and high energy need. DielectricBarrier Discharge (DBD) plasma electro-catalysis may become a solution to overcome the drawbacks in theconventional transesterification process. This process only needs a short time reaction and low energy process.The purpose of this study was to assess the performance of DBD plasma rector in making biodiesel such as: theeffect of high voltage electric value, electrodes gap, mole ratio of methanol / oil, and reaction time. TheResearch method was using GC-MS (Gas Cromatography-Mass Spectrofotometry) and FTIR (FourierTransform Infrared Spectrofotometry) and then it will be analysed the change of chemical bond betweenreactant and product. So, the reaction mechanism can be predicted. Biodiesel is produced using methanol andpalm oil as reactants and DBD plasma used as reactor in batch system. Then, reactants contacted by highvoltage electric. From the results of this research can be concluded that the reaction mechanism occurs in theprocess is the reaction mechanism of cracking, the higher of electric voltage and the longer of reaction time leadto increasing of product yield. The more of mole ratio of methanol / oil and widening the gap between theelectrodes lead to decreased product yield. From this research, product yield maksimum is 89,8% in the variableof rasio mol metanol/palm oil 3:1, voltage 10 kV, electrode gap 1,5 cm, and reaction time 30 seconds.